The Effectiveness of Seey Android Based Game Towards The English Grammar Achievement: English - Meria Anggraeni; Supriyono; Adin Fauzi (Journal of English Development, 2023)
The research intends to examine the effectiveness of SEEY android-based game, an offline English grammar learning application. The research objectives were to discover the strength of the significant value of the effect of SEEY android-based games towards students’ English grammar competence. The grammar material focus on three tenses; simple present, present progressive, and simple past. Applied quasi-experiment as research design with pre-post (test) control group design. The participants were students of the second grade of SMP Negeri 01 Garum. An experimental group was treated by applying SEEY android-based game. A control group was treated by applying the conventional method. The two groups take pretest and posttest to obtain the data. After that the data was analyzed and collected by SPSS application applied t-test formula. The outcomes of the t-test indicated a significance value (0,00) which has less than (0,05). According to the experimental group’s mean score (89,28) was greater than the control group’s (79,16). It was proven that SEEY android-based game as learning media has a significant effect on students’ grammar achievement